Kepuasan Perawat terhadap Pelaksanaan Peran MPP tentang Kontinuitas Pelayanan Pasien - Ristianti, Dwi Anidar; Wijayanti, Catharina Dwiana; Supardi, Sudibyo (Journal of Telenursing (JOTING), 2024)
This study aims to explore nurses' level of satisfaction with the role of MPPs in patient care at Hospital X in Tangerang Regency. The method used was quantitative - qualitative mixed methods. Data analysis used chi square analysis. The results showed that based on the results of quantitative analysis, it appears that the MPP role has a significant positive influence on nurse satisfaction in carrying out patient discharge planning. The results of qualitative analysis through interviews with informants also support quantitative findings. Informants stated that timely assessment and implementation of continuity of patient care for discharge preparation and evaluation of implementation are important factors that can increase nurse satisfaction. The majority of informants expressed satisfaction with the implementation of the MPP role, although there were some who were dissatisfied, which was also in line with the quantitative results. The conclusion of the study that can be drawn is that nurses' satisfaction with the role of the Patient Service Manager (MPP) at Hospital X Tangerang Regency depends on the effectiveness of coordination and integration of services carried out by MPP. Periodic evaluation of the MPP program is needed to improve nurse satisfaction and patient service quality. Keywords: satisfaction, nurses, MPP role, mixed-methods.